2013
DOI: 10.1007/s10973-012-2883-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria in the ErPO4–K3PO4 system

Abstract: The phase equilibria occurring in the ErPO 4 -K 3 PO 4 system were investigated by the thermal analysis, FTIR, and X-ray powder diffraction methods. On the basis of obtained results, the related phase diagram is proposed. This system includes one intermediate compound, K 3 Er(PO 4 ) 2 ; the double phosphate melts incongruently at 1355°C and occurs in two polymorphic forms; transformation b/a-K 3 Er(PO 4 ) 2 proceeds at 420°C. The eutectic occurs at the composition of 58.5 wt% K 3 PO 4 , 41.5 wt% ErPO 4 at 1317… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition, in Refs. [38,45] it has been shown that the thermal effects connected to the formation/ decomposition of Me 3 RE(PO 4 ) 3 are characterized by a large thermal hysteresis. The difference between the onset temperatures of effects on heating and cooling DTA curves is connected to kinetic hindrances occurring by the decomposition/formation of new phases and is a sign of reconstructive-type transformations [45,46].…”
Section: Thermal Behavior Of Ca 3 Y(po 4 )mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in Refs. [38,45] it has been shown that the thermal effects connected to the formation/ decomposition of Me 3 RE(PO 4 ) 3 are characterized by a large thermal hysteresis. The difference between the onset temperatures of effects on heating and cooling DTA curves is connected to kinetic hindrances occurring by the decomposition/formation of new phases and is a sign of reconstructive-type transformations [45,46].…”
Section: Thermal Behavior Of Ca 3 Y(po 4 )mentioning
confidence: 99%
“…Phase diagrams of phosphate systems with rare earth elements have been studied by our group in last decades [34][35][36][37][38][39]. In the Ca 3 (PO 4 ) 2 -REPO 4 systems (RE = Y, La, Ce) form compounds with the formula Ca 3 RE(PO 4 ) 3 [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Their polymorphism has been investigated by plenty of authors (see, e.g. [28][29][30][31][32][33]). Erbium orthophosphate ErPO 4 , is related to the LnPO 4 group with xenotime structure, isostructural to zircon (ZrSiO 4 ) and it crystallizes in the tetragonal system [SG I41/amd, a = 6.8614(5), c = 6.0082(9) Å , Z = 4] [33].…”
Section: Introductionmentioning
confidence: 99%
“…Erbium orthophosphate ErPO 4 , is related to the LnPO 4 group with xenotime structure, isostructural to zircon (ZrSiO 4 ) and it crystallizes in the tetragonal system [SG I41/amd, a = 6.8614(5), c = 6.0082(9) Å , Z = 4] [33]. ErPO 4 exists in one polymorphic form [30].…”
Section: Introductionmentioning
confidence: 99%